Challenges in Distance Education During the (Covid-19) Pandemic Period - Tamer Sari; Funda Nayır (Qualitative Research in Education, 2020)
The purpose of this study is to reveal the perceptions of the teachers, administrators, and academics who had to continue distance education during COVID-19 epidemic disease period, about the problems they experienced and the strategies to cope with the challenges. The working group of the current study consists of 65 teachers. The data were collected via an open-endedwritten interview. Content analysis was applied for analysis of the data gathered. Various important results regarding the use of distance education were obtained during the pandemic period and yielded significant findings. The first and the most important finding is that theachers have difficulties in internet access and lack of infrastructure, classroom management and human resources. Another challenge that participants reported was about teachers’ and students’ behaviours. The last theme stated by the participants is the distance education process itself. The findings reveal that the participants determined their strategies to deal with these problems with new arrangements regarding the classroom management, getting help from colleagues, family members and experts and communicating with students and parents. It can be certainly suggested that the participants are not ready for the distance education process and there is a lack of application in this regard; such as technology support and distance education training, and moreover, the participants do not have sufficient knowledge and experience about distance education.